1992
DOI: 10.1002/mrm.1910260211
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy of human brain: Applications to normal white matter, chronic infarction, and MRI white matter signal hyperintensities

Abstract: A modified ISIS method, for image-selected localized proton magnetic resonance spectroscopy (1H MRS), was used to determine the ratios and T2 relaxation times of proton metabolites in normal subjects and in patients with chronic infarction and MRI white matter signal hyperintensities (WMSH). First, in patients with cerebral infarctions, increased concentrations of lactate were found in the majority of patients, and N-acetyl aspartate (NAA) was reduced to a significantly greater extent than choline (Cho) or cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 42 publications
(18 reference statements)
6
64
3
Order By: Relevance
“…2 However, other studies found either an increase 5,6 or a decrease in choline levels 7,8 in stroke lesions. Discrepancies might be related to individual variability, the small sample sizes of 10 patients or less in some studies, 5,7 or to the use of different patients scanned at different time points rather than the same patients scanned at similar times. 8 The current study is the largest to date following the same group of patients with stroke longitudinally using proton MR spectroscopic imaging at fixed time points to reduce this variability.…”
Section: Discussionmentioning
confidence: 95%
“…2 However, other studies found either an increase 5,6 or a decrease in choline levels 7,8 in stroke lesions. Discrepancies might be related to individual variability, the small sample sizes of 10 patients or less in some studies, 5,7 or to the use of different patients scanned at different time points rather than the same patients scanned at similar times. 8 The current study is the largest to date following the same group of patients with stroke longitudinally using proton MR spectroscopic imaging at fixed time points to reduce this variability.…”
Section: Discussionmentioning
confidence: 95%
“…However, as we have discussed before, a large part of the lactate signal overlapped with lipid signals in conventional MRS measurements (Kimura et al, 2001;Shimizu et al, 1996). Thus, lactate has been thought to rise early after the insult in the acute phase (<24 h) and may remain high over a long period into the chronic phase (>7 days) (Sappey-Marinier et al, 1992), which could lead us to an inappropriate understanding of the pathophysiological status in the ischemic lesion. In the present study, we could measure isolated lactate signals in the ischemic lesion, demonstrating that they rapidly rise after stroke but disappear within several days.…”
Section: Discussionmentioning
confidence: 99%
“…Proton MR spectroscopy is a noninvasive method that allows measurement of various metabolites in vivo, such as choline-containing compounds (Cho), creatine and creatine phosphate (Cr), N-acetyl aspartate (NAA), and pathologic levels of lactate (Bottomleym, 1987;Frahm et al, 1989;Sappey-Marinier et al, 1992). Detection of lactate by in vivo proton magnetic resonance spectroscopy may provide a means of identifying regions of metabolic stress in brain and other human tissue, potentially identifying regional ischemia in stroke (Federico et al, 1994;Saunders, 2000;Schwarcz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Key Words: nuclear magnetic resonance Ⅲ lipids Ⅲ lactic acid Ⅲ cerebral infarction Ⅲ cerebrovascular accident I n vivo proton magnetic resonance spectroscopy (MRS) has consistently detected elevated brain lactate after human stroke that may persist for many months. [1][2][3][4][5] The origin and significance of this lactate may vary at different times during the evolution of the infarct. While lactate is produced acutely by ischemia, lactate seen beyond the first 72 hours may reflect the presence of macrophages and other leukocytes.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] The origin and significance of this lactate may vary at different times during the evolution of the infarct. While lactate is produced acutely by ischemia, lactate seen beyond the first 72 hours may reflect the presence of macrophages and other leukocytes.…”
mentioning
confidence: 99%